Future of Irrigation in Agriculture in Southern Europe - Iván Francisco García-Tejero; Víctor Hugo Durán-Zuazo (Agriculture, 2022)
Water is the most limiting natural resource in many Mediterranean areas of southern Europe, and this, together with the actual scenario of climate change (CC), promotes a framework of uncertainty and creates major challenges concerning the sustainability and viability of the current agro-ecosystems [...]